Genetic analysis of ring finger protein 213 (RNF213) c.14576G>A polymorphism in patients with vertebral artery dissection: a comparative study with moyamoya disease. (2nd September 2019) - Tashiro, Ryosuke; Fujimura, Miki; Sakata, Hiroyuki; Endo, Hidenori; Tomata, Yasutake; Sato-Maeda, Mika; Niizuma, Kuniyasu; Tominaga, Teiji
ABSTRACT: Background : Intracranial vertebral artery dissection (VAD) and moyamoya disease (MMD) are rare cerebrovascular diseases, both of which have an ethnic predominance in the East Asian population. Disruption of the internal elastic lamina and subsequent rupture of the medial layer result in intracranial VAD. MMD is a chronic occlusive cerebrovascular disease of unknown etiology, in which the medial layer and internal elastic lamina of the intracranial arteries are significantly compromised. Recent genetic studies found ring finger protein 213 (RNF213) to be an important susceptibility gene for MMD in East Asian patients, but the association between VAD and RNF213 has not been investigated. . Methods : We investigated polymorphism of the RNF213 gene (c.14576G>A) in genomic DNA of 24 patients with intracranial VAD in comparison with 58 patients with definitive MMD and 48 healthy controls. Results : Although RNF213 gene polymorphism (c.14576G>A) was evident in 69% of the MMD patients (40/58), none of the patients with intracranial VAD had this characteristic polymorphism (0/24, p  < 0.001). The incidence of RNF213 c.14576G>A polymorphism was 4.2% in healthy controls (2/48). After adjustment by age and sex, the incidence of RNF213 c.14576G>A was significantly lower in intracranial VAD patients ( p  = 0.021) than that in MMD patients. Conclusions : In contrast to MMD patients, the prevalence of RNF213 c.14576G>A polymorphism was significantly lower in patients with intracranial VAD. The RNF213 gene polymorphism may preferentially affect the cerebrovascular lesion in the anterior circulation, which is originated from the primitive internal carotid arteries. The genetic background underlying intracranial VAD should be elucidated in future studies. Abbreviations : VAD: vertebral artery dissection; MMD: moyamoya disease; RNF213: ring finger protein 213 ; CAD: carotid artery dissection